FILSAFAT MANUSIA DALAM ILMU PENGETAHUAN SYARIAH DI LINGKUNGAN SOSIAL KEAGAMAAN INDONESIA - Fahrany, Sofia; Mamang, Damrah; Huwaida, Hasna'; Sirojuddin, Sirojuddin; Yasin, Rahman (Spektra: Jurnal Ilmu-ilmu Sosial, 2025)
Human philosophy is a servant of Allah SWT who has the task of preaching to command goodness and avoid the prohibitions of Allah as stated in the At-Tahrim Letter verse 6 "Protect yourselves and your families from the fire of hell". Humans as believers or people who believe should ensure the improvement and enhancement of their personal lives. Islam is not a religion that only consists of dogma, worship and ceremonies. Islam is actually a complete way of life, which guides humans according to the guidance given by Allah to His Messenger, Muhammad. Islam is a system and rule of life.the spiritual and moral values ​​taught by sharia. Islamic legal system derived from the Qur'an and Sunnah. Sharia regulates various aspects of human life, from worship, muamalah (social interaction), to social sharia. The philosophy of a knowledgeable or knowledgeable person is an achievement that is in the process of seeking the ultimate truth. This article will discuss the relationship between humans and sharia, and how sharia guides humans towards a blessed life in social society. To answer this problem, the researcher uses a qualitative descriptive research method through library data such as online journals, e-books and scientific books, law of books, yuridis normatif in order to obtain systematic, good and correct results. The social benefits of religion are building solidarity and unity, increasing community welfare, maintaining harmony between religious communities.